2006
DOI: 10.1111/j.1559-4564.2006.05626.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Myocyte Remodeling and Fibrosis in the Cardiometabolic Syndrome

Abstract: Myocardial cellular and extracellular matrix remodeling are important in the development of left ventricular hypertrophy and are essential for the adaptive and maladaptive changes associated with the cardiometabolic syndrome. This brief review of myocyte remodeling also presents preliminary observational findings regarding myocardial adaptive hypertrophy remodeling, including an increase in mitochondria and capillaries, convolutions and lengthening of intercalated discs, the addition of sarcomeres, thickened Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…The pathophysiology of diabetic cardiomyopathy is multifactorial, and major reason has been attributed to persistent hyperglycemia (11). Hayden et al (12) showed that high glucose levels have been shown to induce myocardial fibrosis in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of diabetic cardiomyopathy is multifactorial, and major reason has been attributed to persistent hyperglycemia (11). Hayden et al (12) showed that high glucose levels have been shown to induce myocardial fibrosis in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The male transgenic heterozygous (mRen2)27 (Ren2) rat overexpresses the mouse renin gene and is known to have increased local tissue levels of angiotensin II (Ang II), low plasma renin activity and increased plasma levels of aldosterone [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15]. Transgenic Ren2 rats manifest an activated renin-angiotensin-aldosterone system (RAAS) and altered autonomic nervous system regulation [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…By limiting our discussion to these particular end-organs, we did not go into any in-depth discussion of the cardiovascular system, retina, neuronal systems (brain or peripheral neuronal unit), kidney or ovary. The following references may be helpful to those who wish to learn more about those end-organ systems that were not included in this discussion [30,39,40,109,110,111,112,113,114,115,116,117]. …”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Further, this mechanism may be responsible for the early findings of pericapillary and perivascular fibrosis in the Ren2 model of hypertension and insulin resistance, which manifests tissue overexpression of the mouse renin gene [37,38,39,40]. …”
Section: Vascular Endothelial Dysfunction As a Critical Abnormality Imentioning
confidence: 99%
See 1 more Smart Citation